Development of an actuated corrugated laminate for morphing structures. (17th January 2021) - Airoldi, A.; Rigamonti, D.; Sala, G.; Bettini, P.; Villa, E.; Nespoli, A.
ABSTRACT: This paper presents the design, manufacturing and experimental assessment of a morphing element consisting of a composite corrugated panel that hosts a diffused actuation system based on Shape Memory Alloy (SMA) actuators. The characterisation of the SMA actuators is reported and the system performance is predicted through an analytical model and finite element analyses. Two versions of the actuated system are proposed, with different methods for the physical integration of the SMA wires into the composite part. Manufacturing and testing of specimens with different wire densities are reported. Correlation with experiments validates the analytical and numerical approaches adopted for the design and analyses. The results confirm the potential of the concept proposed for developing corrugated panels that can be contracted in a predefined direction by a load-bearing actuation system, but still retain high stiffness and strength properties in other directions.